Immunotherapy of triple-negative breast cancer with cathepsin D-targeting antibodies. Issue 1 (4th February 2019) - Ashraf, Yahya; Mansouri, Hanane; Laurent-Matha, Valérie; Alcaraz, Lindsay B.; Roger, Pascal; Guiu, Séverine; Derocq, Danielle; Robin, Gautier; Michaud, Henri-Alexandre; Delpech, Helène; Jarlier, Marta; Pugnière, Martine; et al.
Abstract : Background: Triple-negative breast cancer (TNBC) treatment is currently restricted to chemotherapy. Hence, tumor-specific molecular targets and/or alternative therapeutic strategies for TNBC are urgently needed. Immunotherapy is emerging as an exciting treatment option for TNBC patients. The aspartic protease cathepsin D (cath-D), a marker of poor prognosis in breast cancer (BC), is overproduced and hypersecreted by human BC cells. This study explores whether cath-D is a tumor cell-associated extracellular biomarker and a potent target for antibody-based therapy in TNBC. Methods: Cath-D prognostic value and localization was evaluated by transcriptomics, proteomics and immunohistochemistry in TNBC. First-in-class anti-cath-D human scFv fragments binding to both human and mouse cath-D were generated using phage display and cloned in the human IgG1 λ format (F1 and E2). Anti-cath-D antibody biodistribution, antitumor efficacy and in vivo underlying mechanisms were investigated in TNBC MDA-MB-231 tumor xenografts in nude mice. Antitumor effect was further assessed in TNBC patient-derived xenografts (PDXs). Results: High CTSD mRNA levels correlated with shorter recurrence-free survival in TNBC, and extracellular cath-D was detected in the tumor microenvironment, but not in matched normal breast stroma. Anti-cath-D F1 and E2 antibodies accumulated in TNBC MDA-MB-231 tumor xenografts, inhibited tumor growth and improved mice survival without apparent toxicity. The Fc function of F1, the best antibody candidate, was essential for maximal tumor inhibition in the MDA-MB-231 model. Mechanistically, F1 antitumor response was triggered through natural killer cell activation via IL-15 upregulation, associated with granzyme B and perforin production, and the release of antitumor IFNγ cytokine. The F1 antibody also prevented the tumor recruitment of immunosuppressive tumor-associated macrophages M2 and myeloid-derived suppressor cells, a specific effect associated with a less immunosuppressive tumor microenvironment highlighted by TGFβ decrease. Finally, the antibody F1 inhibited tumor growth of two TNBC PDXs, isolated from patients resistant or not to neo-adjuvant chemotherapy. Conclusion: Cath-D is a tumor-specific extracellular target in TNBC suitable for antibody-based therapy. Immunomodulatory antibody-based strategy against cath-D is a promising immunotherapy to treat patients with TNBC.